Recognition of Adat Forest and Plantation Concessions in Indonesia - Esmi Warassih; Sulaiman Sulaiman (Kanun Jurnal Ilmu Hukum, 2017)
ABSTRACT: Legal recognition of adat forests has long been established through Decision of the Constitutional Court No. 35/PUU-X/2012 correcting terminology of adat forests in the Forestry Law. However, the recognition has been still not running as expected to date. This article will explore about what are legal implications of recognition of adat forests associated with plantation concessionaires. The study found a number of unfair articles in the Plantation Act, even though they had been corrected by two Decisions of the Constitutional Court. The injustice appeared in regulation to plantation concessionaires who can be entitled to land for plantation business. On the one hand, such regulation showed injustice, especially with orientation of partiality. On the other hand, it would potentially generate a conflict between plantation business and community. A number of cases occurred between communities and plantation enterprises are potentially taking small community away from justice. Pengakuan Hutan Adat dan Konsesi Perkebunan di Indonesia ABSTRAK: Pengakuan hukum atas hutan adat sudah lama diteguhkan, melalui Putusan Mahkamah Konstitusi Nomor 35/PUU-X/2012, yang mengoreksi terminologi hutan adat dalam Undang-Undang Kehutanan. Akan tetapi hingga sekarang pengakuan tersebut masih belum berjalan sebagaimana yang diharapkan. Artikel ini ingin menelusuri bagaimana implikasi hukum atas pengakuan hutan adat terhadap pemegang konsesi perkebunan. Penelitian ini menemukan bahwa dalam Undang-Undang Perkebunan, terdapat sejum-lah pasal yang tidak berkeadilan, walau sudah diperbaiki dengan dua Putusan Mahka-mah Konsitusi. Ketidakadilan tampak pada pengaturan pelaku usaha perkebunan yang dapat diberi hak atas tanah untuk usaha perkebunan. Pengaturan demikian memperlihatkan ketidakadilan di satu pihak, terutama dengan orientasi keberpihakan. Di pihak lain, berpotensi memunculkan konflik usaha perkebunan dengan masyarakat. sejumlah kasus terjadi antara masyarakat dan usaha perkebunan, yang berpotensi menjauhkan masyarakat kecil dari keadilan.